Comprehensive multicultural education theory and practice - Bennett, Christine I. (Allyn and Bacon, 1995)
Booknews, Inc.: Helps practicing and prospective teachers bridge the gap between multicultural concepts and practice in areas such as classroom management, instructional strategies, and curriculum development. Defines multicultural education, and treats assimilation and pluralism among various groups in the US, learning styles, and teaching strategies. Offers numerous guidelines and specific lesson plans for a multicultural curriculum. This third edition contains new material on European Americans, African Americans, and Muslims and Arab Americans.